Induction Motor Direct Torque Control with Synchronous PWM - Alessandro Benevieri; Gianmarco Maragliano; Mario Marchesoni; Massimiliano Passalacqua; Luis Vaccaro (Energies, 2021)
A novel induction motor direct torque control (DTC) algorithm with synchronous modulation is presented. Compared to the traditional DTC method, whose main drawback is the presence of low-frequency torque harmonics (sub-harmonics), in the proposed method, the PWM switching frequency is imposed to be an integer multiple of the main supply frequency. This is achieved by continuously adjusting the PWM switching period to significantly reduce low-frequency harmonics. The devised algorithm has been tested on an inverter-fed induction motor drive system, and the obtained results show an important reduction of the sub-harmonic spectral content of the developed torque with respect to a conventional direct torque control while maintaining at the same time a high dynamic response.